2022
DOI: 10.1002/aenm.202202584
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic and Quantitative Understanding of the Interactions between SiO and Graphite Particles

Abstract: SiO, comprised of silicon and silicon dioxides (SiO2), is one of the most commercially promising anode materials to mix with current widely used graphite for the high energy density lithium‐ion batteries (LIBs). One of the major bottlenecks for SiO/Graphite (SiO/Gr) composite anode is the cyclability due to considerable stress and strain (deformation) caused within and among the composite particles. However, a sophisticated and quantitative understanding of the highly electrochemical–mechanical coupling behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…The accumulation of mechanical stresses can lead to fatigue and damage of electrode materials, resulting in reduced battery performance and lifespan. Gao et al 65 validated an electrochemo−mechanical model to reveal the potential control mechanisms for SiO/graphite. The results demonstrate that 8−10 wt % SiO is an optimization for cycle life at 1 C. In addition, positioning SiO near the separator and decreasing particle size has been found to benefit electrochemical performance without significantly affecting the mechanical mismatch.…”
Section: Methodsmentioning
confidence: 99%
“…The accumulation of mechanical stresses can lead to fatigue and damage of electrode materials, resulting in reduced battery performance and lifespan. Gao et al 65 validated an electrochemo−mechanical model to reveal the potential control mechanisms for SiO/graphite. The results demonstrate that 8−10 wt % SiO is an optimization for cycle life at 1 C. In addition, positioning SiO near the separator and decreasing particle size has been found to benefit electrochemical performance without significantly affecting the mechanical mismatch.…”
Section: Methodsmentioning
confidence: 99%
“…These interfacial encapsulation strategies can be generally classified into three categories according to the Li + /e – transport characteristics, as follows: Physical coating layer that contributes to enhance the e – conductivity (Figure a). In this case, various carbon materials such as graphite, amorphous pyrolytic carbon, graphene, , and carbon nanotubes have been employed via physical mixing such as mechanical ball milling, spray drying, etc. But, due to the weak physical binding between carbon and SiO, effective ICT is retarded or even obstructed.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, for the SiO/Gr anode battery, a few works have been performed to explore the EIS properties correlating to SOC and SOH. Meanwhile, Xu et al [20] established a multi-physics models to quantitatively investigate the interaction of SiO/Gr anode, the results demonstrated that an 8-10 wt.% of SiO is an optimal choice for the composite anode. Manthiram et al [8] proposed that there is a crossover effect between silicon particles and graphite particles, which can have an impact on the performance of LIBs.…”
Section: Introductionmentioning
confidence: 99%